A Framework to Enhance Public Health and Wellbeing through Urban Green Spaces - Gupta, Pranav; Agarwal, Divya S. (Calibrating Urban Livability in the Global South, 2024)
The study aims to address the gap by developing a framework identifying key parameters of urban green spaces that enhance public health and wellbeing in smart cities. A rigorous review of existing literature and empirical data analysis was conducted to identify parameters such as the size, location, design, and biodiversity of green spaces, as well as the availability of amenities within them. The study explored various attributes affecting and impacting the urban green spaces in a city. A bibliometric analysis was conducted to achieve major attributes which were again refined according to the study and then were reduced to 7 attributes which have a direct connect with people, their connect to such spaces and its social viability. Priority based weights were given to the attributes and they ranked accordingly. Proximity to public green space was given Rank 1 with extent of urban green space as Rank 2, interactive activities was given Rank 3, perceived security through green spaces was ranked as 4, maintenance of urban green spaces was ranked as 5, building proximity to green spaces was ranked as 6 and lastly, the 7th rank was given to integration of blue landscapes. After the ranking was done, a renowned case from the New York was selected to validate the achieved attributes and check their relevance. It was concluded that the attributes were perfectly applicable to the case. It was inferred that people are affected by urban green spaces and their presence directly affects their health and wellbeing.